Urban horror : neoliberal post-socialism and the limits of visibility - Huang, Erin Y. (Erin Yu-Tien), 1981- (Sinotheory., 2020)
"Urban Horror offers a theory of neoliberal post-socialism through an examination of Chinese cinema. According to Erin Huang, neoliberal post-socialism is the economic order that succeeded the end of the Cold War, and describes the attempted articulation of geopolitical and economic relations between formerly socialist and non-socialist countries in what Huang terms the era of the 'post' or 'post-X.' Rather than describing the definitive end of an era, 'post-X' proffers a regressive temporal logic that sutures the present to the past and continuously differs the future. Huang sees the proliferation of terms to describe Chinese economics after the 1978 economic reform policies as the symptoms of a geopolitical order that doesn't yet have a properly articulated name. For Huang, this unarticulated political order is nevertheless felt affectively through what she calls 'urban horror, ' and it is best accessed through the cinema of the time period, in which hypermediality-when the meaning of the image no longer depends on an externally existing reality-became popular. Drawing on a definition of horror as a historical mode of perception that occurs when a perceived external reality exceeds one's internal frame of comprehension, Huang argues that the excess of feeling that marks horror's presence allows for an 'elusive sensory communicative channel' in which alternative and dissenting political feelings can emerge. Chapter 1 offers a historical study of the factory in cinema, positioning the images of factory ruins in Chinese cinema as an attempt to reinvent a past that never fully existed. Chapter 2 examines urban horror from a post-socialist feminist perspective by examining the films of Shaohong Li. Chapter 3 focuses on urban horror's development as a product of time in post-socialist Chinese documentary films. Chapter 4 focuses on post-1997 Hong Kong cinema that circulates public sentiments about Hong Kong as a place of political and economic exception. Chapter 5 examines the films of Ming-liang Tsai-and the subject of precarity in Tsai's films-in relation to their display in art museums and performance art spaces. This book will be of interest to students and scholars of Sinophone and East Asian studies, film studies, studies of globalization and neoliberalism, political and social theory, affect studies, feminist studies, and Marxist studies"--